2011
DOI: 10.1016/j.biopsych.2011.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Brain-Derived Neurotrophic Factor Is Predictive of Cocaine Relapse Outcomes: A Prospective Study

Abstract: Background Cocaine dependence is associated with high relapse rates but few biological markers associated with relapse outcomes have been identified. Extending preclinical research showing a role for central Brain Derived Neurotrophic Factor (BDNF) in cocaine seeking, we examined whether serum BDNF is altered in abstinent, early recovering, cocaine-dependent individuals and if it is predictive of subsequent relapse risk. Methods Serum samples were collected across three consecutive mornings from 35 treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 35 publications
2
55
2
Order By: Relevance
“…Our finding of sustained elevation of BDNF plasma levels in women with cocaine dependence is consistent with those of many previous clinical and preclinical reports. 4,6,17,19 A consistent body of evidence stemming from rat models has indicated that elevated BDNF plays an important role in the enhancement of mesolimbic DA neuronal function, which could be related both to increased drug seeking behaviour/ craving and to the reward effect of the drug. 47 The role of DA is primarily in the reinforcing effects of drugs and the motivation to obtain them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our finding of sustained elevation of BDNF plasma levels in women with cocaine dependence is consistent with those of many previous clinical and preclinical reports. 4,6,17,19 A consistent body of evidence stemming from rat models has indicated that elevated BDNF plays an important role in the enhancement of mesolimbic DA neuronal function, which could be related both to increased drug seeking behaviour/ craving and to the reward effect of the drug. 47 The role of DA is primarily in the reinforcing effects of drugs and the motivation to obtain them.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Because preclinical evidence has suggested a potential role of these endogenous peptides in mediating the behavioural effects related to substance administration 5 and drug-induced neuro adaptation, 6 recent studies have explored neurotrophin expression in humans 4,7,8 to better comprehend the neurobiological and circuit underpinnings of addiction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first study assessing BDNF in cocaine addicts found no difference in BDNF serum levels in 15 cocaine addicts and a group of healthy controls (Angelucci et al, 2007). However, a recent cross-sectional study of 22 cocaine-dependent individuals reported a significant correlation between serum BDNF and number of abstinence days (Hilburn et al, 2011) and recently, BDNF was reported to be increased after 3 weeks of withdrawal (D'Sa et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In support of this idea, available evidence indicates that in recovering cocaine-dependent individuals, elevated BDNF serum levels predicted shorter subsequent time to relapse, higher total cocaine use, and cocaine craving (D'Sa et al 2011;Corominas-Roso et al 2012). In conjunction, laboratory animals display a progressive increase in Bdnf protein levels in mesolimbic areas, including the PFC (Grimm et al 2003;McGinty et al 2010;Pickens et al 2011) following prolonged abstinence.…”
Section: Neurobiology Of Cocaine Addictionmentioning
confidence: 93%